Subepithelial Corneal Deposits Associated with Exemestane. (27th June 2020) - Amireskandari, Annahita; Nguyen, Elena; Hinkle, David; Mauger, Thomas
Abstract : This is a case report of corneal deposits noted in a 69-year-old female patient taking the aromatase inhibitor, exemestane, after undergoing a mastectomy and chemotherapy for breast cancer. The patient presented to our eye clinic for a new-onset floater in one eye, and bilateral subepithelial opacities were found incidentally on exam. The patient completed a 5-year course of the medication shortly after her initial visit with us and was noted to have a slight improvement in the density of the opacities on a follow-up visit 3 months later. We believe these corneal changes were most likely secondary to exemestane. The effect of aromatase inhibitors on the eye deserves further exploration as an increasing number of patients are prescribed these medications.